English in Mathematics : Trends, Benefits, and Challenges in Southeast Asia Countries - Syafi'i, Moh. Thoyib; Hidayat, Angga; Kusumaningsih, Ani; Friska, Yuliana; Nurmalia, Nurmalia (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to identify the application of English in mathematics teaching in Southeast Asia countries, focusing on trends across countries, methods, benefits, and challenges. This study employed a systematic literature review (SLR) method adapted from the PRISMA model, resulting in 17 relevant articles obtained from 141 articles in the Scopus and Web of Science databases.Â The data analysis technique of this research applied thematic analysis to review, identify, and analyze the data.Â The findings revealed that emerging research focused on learning policies and media, improving pedagogical practices, educational quality, and student learning outcomes. Malaysia is the country that has conducted the most research on this topic, with 11 articles, followed by the Philippines and Thailand, each with 2 articles. The majority of studies used qualitative methods and mixed methods. The benefits of using English in mathematics instruction included avoiding translation errors, supporting the implementation of global learning, enhancing soft skills and problem-solving abilities, supporting future career prospects, and improving the quality of learning with support from teachers and related parties. Some challenges faced include varying skills and readiness of teachers and students, the availability and utilization of resources, and the different impacts on students, especially those from diverse demographics. Additionally, cultural and linguistic gaps between English and studentsâ€™ mother tongue, the rapid adoption of English policies in mathematics teaching, and necessary pedagogical adjustments also present challenges.